MODERNIZATION OF THE SYSTEM FOR PREPARING PHYSICAL EDUCATION SPECIALISTS FOR PROFESSIONAL CAREER ACTIVITIES - Xolboeva Gulxayo Xolboevna (Research Focus International Scientific Journal, 2025)
Like any area of the social sphere, physical education and sports require financial costs, but through the social influence obtained, it covers the costs spent on production in the field of sports many times. Physical education and sports expenses-this is the investment in human health, which determines the quality of the country's labor resources. However, today the effectiveness of the physical education system and the sphere that constitutes it requires a lot of processes. The functioning and further development of the field of "Physical Culture "in the conditions of a modern market economy involves the constant search for additional sources of financing, innovative means of competitive struggle, market relations.